The roles of organizational culture toward employee engagement: a case of manufacturing company in Malaysia (CTRM Aero Composites Sdn. Bhd.) / Ain’ Nur Habib Hakim@Abu - Hakim@Abu, Ain’ Nur Habib (Faculty of Business and Management, 2016)
Employee engagement has been a global issue recently in order for organization to strive for success. Employee engagement is defined as commitment and emotional attachment of an employee or group towards the organization. Organizational culture is one of the factor that contribute to employee engagement. Henceforth, the purpose of this research is to identify what are the roles of organizational culture (clan, adhocracy, hierarchy, and market) toward employee engagement in a manufacturing company in Malaysia. This research is a quantitative research which used questionnaire as an instrument to collect data. The data had been successfully collected from 127 respondents out of 190 as a total population in CTRM Aero Composites Sdn. Bhd. by using convenience sampling method. Then, all data were analyzed and interpreted by using Statistical Package for the Social Sciences (SPSS) software. Thus, Pearson Correlation analysis indicates that the strength of association of clan, adhocracy, hierarchy, and market culture are weak. Apart from that, regression analysis shows that there is a positive and significant relationship between clan, adhocracy, and market culture toward employee engagement. Meanwhile, hierarchy culture shows no significant relationship towards employee engagement. In addition, the most significant of organizational culture toward employee engagement is adhocracy culture.